Gut barrier breach and glucose dysregulation: the dual threat of food-transformed microplastics - Zhe Chen; Yihua Yuan; Chuxin Zhang; Xu Li; Fei Ren; Dingchang Xue; Juan Shao; Keming Yun; Zhongyuan Guo (Food Research International, 2026)

Integrated whole-transcriptome analysis reveals ceRNA network dysregulation underlying methcathinone-induced synaptic damage and cognitive impairment - Rukui Zhou; Chunming Xu; Zhe Chen; Jieping Lv; Keming Yun; Zhiwen Wei (Food and Chemical Toxicology, 2026)

Hydrodynamics acts as a key driver of microplastics transport throughout surface and surface-subsurface water interaction zones: A mechanistic review and research priorities - Xiaohua Huang; Yuchuan Meng; Yu Chen; Peng Zhao; Li Liu; Keming Tang (Journal of Hazardous Materials, 2026)

Chronic exposure to Bisphenol AF from gestation through adulthood induces renal injury in 8-month-old mice via lipid metabolism dysregulation and ferroptosis - Rui Gao; Jiangsong Ma; Aonan Lu; Xiaoyun Wu; Chao Zhang; Keming Yun; Zhe Chen; Xiaotong Ji (Journal of Hazardous Materials, 2026)

IP3R1 regulates AMPK-mTOR-mediated mitochondrial function to influence the oocyte-to-embryo transition of porcine - Ran Teng; Ning Xu; Xingfu Chen; Yuening Xing; Xiaoqing Sun; Dexin Yuan; Keming Huang; Lepeng Gao; Suo Li (Theriogenology, 2026)

Study on the daytime heat gain and nighttime heat dissipation characteristics of microchannel PV/T modules - Keming Xu; Rongji Xu; Hongbing Chen; Gaochao Li; Ziyu Xing (Energy and Buildings, 2026)

Corrigendum to “Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture” [Chem. Eng. J. 527 (2026) 171623] - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Engineering high-fertility synthetic apomixis in hybrid rice via genome editing of MiMe and OspPLAIIκ - Chaolei Liu; Yuye Chen; Tingting Sun; Jian Wang; Huan Liang; Keming Zhu; Qian Qian; Kejian Wang (Science China Life Sciences, 2026)

Roxithromycin disrupts nitrogen uptake and stress responses in wheat under nitrogen deficiency - Binbin Yu; Yier Yang; Keming Yang; Chunyu Jiang; Zefeng Yang; Yiru Zhao; Xiaoli Wang; Beibei Shen; Shaohu Ouyang; Zhongzhi Chen (Plant and Soil, 2026)

From protein-like to humic-like substances: Feed-derived regulation of dissolved organic matter transformation in RAS - Ying Bai; Ruijie Ma; Zhengguo Cui; Hao Li; Hongwu Cui; Yong Xu; Jianlei Chen; Keming Qu (Aquacultural Engineering, 2026)

Unveiling the mechanism: DOM from chemically pretreated corncobs drives denitrification via mediating microbial community succession - Ying Bai; Ruijie Ma; Zhengguo Cui; Hongwu Cui; Weiman Gong; Wei Dong; Hao Li; Yong Xu; Jianlei Chen; Keming Qu (Journal of Environmental Chemical Engineering, 2026)

Correlation analysis of heavy metal, antibiotics accumulation, and antibiotic resistance genes induced by long-term biogas slurry application - Binbin Yu; Chunyu Jiang; Keming Yang; Yang Zhang; Yang Gao; Zhongzhi Chen; Xiaoqing Qian; Shaohu Ouyang (Journal of Environmental Management, 2026)

Adaptation Mechanisms of Aquatic Animals to Saline–Alkaline Water Aquaculture: Physiological, Energetic and Molecular Perspectives - Yingsha Qu; Huichen Li; Bo Zhang; Hongwu Cui; Jianlei Chen; Yong Xu; Zhengguo Cui; Keming Qu; Hao Li (Fishes, 2026)
Saline–alkaline water constitutes a vital strategic non-traditional fishery resource in China, characterized by high pH values, elevated carbonate alkalinity, and complex ionic compositions. These extreme environmental conditions impose significant stress on aquatic animals, mainly by inducing ionic toxicity and disrupting acid–base regulatory mechanisms. Such disruptions subsequently lead to osmotic imbalance, metabolic dysregulation, and immunosuppression, thus restricting the survival and growth of aquatic species in aquaculture systems. Consequently, the sustainable development of the saline–alkaline aquaculture is imperative for enhancing production efficiency and promoting the utilization of marginal land and water resources. This review comprehensively summarizes the current status of saline–alkaline aquaculture and highlights the stress-inducing impacts of salinity, alkalinity, and specific ionic ratios on teleost fishes and crustaceans. It further explores key adaptive mechanisms, including osmoregulatory and ionoregulatory strategies, bioenergetic trade-offs related to oxygen consumption and ammonia excretion, coordinated antioxidant and innate immune responses, as well as recent findings from multi-omics research. This review aims to offer a scientific foundation for the selection and breeding of saline–alkaline-tolerant strains, the precise regulation of aquaculture water environments, and the development of ecological aquaculture models in saline–alkaline regions, thereby facilitating the sustainable utilization of saline–alkaline land and water resources.

Numerical study on three-dimensional coupling characteristics for electromagnetism and flow in flat linear induction pump - Heyao Li; Zhuqian Zhang; Lixin Yang; Keming Bi; Xin Yan; Haojie Zhang; Xiao Chen (Annals of Nuclear Energy, 2026)

Optimizing shrimp growth and water quality in constructed wetland recirculating aquaculture systems: Effects of stocking density and shrimp size - Meimei Hu; Yanyan Wang; Jianlei Chen; Hongwu Cui; Shengmin Zhu; Tongtong Jin; Keming Qu; Zhengguo Cui (Aquaculture, 2026)

Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Synergistic enhancement of emamectin benzoate and Metarhizium anisopliae against late-instar Spodoptera frugiperda by promoting fungal pathogenicity - Tingting Cao; Rongrong Qiu; Jing Chen; Mi Kuang; Keming Wu; Yuxian Xia; Guoxiong Peng (Pesticide Biochemistry and Physiology, 2025)

Restoring plant diversity on Loess Plateau mining slopes: effects of artificial soil and slope characteristics with management strategies - Zhang Chen; Oumeng Qiao; Keming Ma; Ziqiang Du (Journal of Environmental Management, 2025)

Longitudinal analysis of metabolic liver disease induced by high-starch diets in largemouth bass (Micropterus salmoides) - Xixuan Huang; Xuemei Ouyang; Li Wang; Kun Xue; Haodong Yu; Chenlei Liao; Feifei Chen; Keming Rong; Xuezhen Zhang (Aquaculture International, 2025)

Impact of Water Velocity on Litopenaeus vannamei Behavior Using ByteTrack-Based Multi-Object Tracking - Jiahao Zhang; Lei Wang; Zhengguo Cui; Hao Li; Jianlei Chen; Yong Xu; Haixiang Zhao; Zhenming Huang; Keming Qu; Hongwu Cui (Fishes, 2025)
In factory-controlled recirculating aquaculture systems, precise regulation of water velocity is crucial for optimizing shrimp feeding behavior and improving aquaculture efficiency. However, quantitative analysis of the impact of water velocity on shrimp behavior remains challenging. This study developed an innovative multi-objective behavioral analysis framework integrating detection, tracking, and behavioral interpretation. Specifically, the YOLOv8 model was employed for precise shrimp detection, ByteTrack with a dual-threshold matching strategy ensured continuous individual trajectory tracking in complex water environments, and Kalman filtering corrected coordinate offsets caused by water refraction. Under typical recirculating aquaculture system conditions, three water circulation rates (2.0, 5.0, and 10.0 cycles/day) were established to simulate varying flow velocities. High-frequency imaging (30 fps) was used to simultaneously record and analyze the movement trajectories of Litopenaeus vannamei during feeding and non-feeding periods, from which two-dimensional behavioral parameters—velocity and turning angle—were extracted. Key experimental results indicated that water circulation rates significantly affected shrimp movement velocity but had no significant effect on turning angle. Importantly, under only the moderate circulation rate (5.0 cycles/day), the average movement velocity during feeding was significantly lower than during non-feeding periods (p

Unraveling Spiroplasma eriocheiris: Morphological motility, virulence mechanisms, and host defense strategies in crustacean pathogenesis - Siyuan Zhang; Jiaxin Chen; Yalan Jiang; Yan Li; Chenbin Zhu; Yujun Tang; Yaqi Wang; Hong Huang; Keming Zhong; Yingrui Xiong; Jiaofeng Peng; Peng Liu (Aquaculture, 2025)

A clean utilization process for low-grade ball Clay: Preparation of PAFS and applications in LC3 - Longxin Zhao; Yi'an Li; Yuxuan Wang; Zihan Chen; Keming Chen; Ruifeng Guo; Cundi Wei; Wenqing Li; Fagui Qiu; Shiding Miao (Journal of Cleaner Production, 2025)

Lipid droplet-targeting fluorescent probes for monitoring hydrogen sulfide in ferroptosis - Chen Wang; Zhaomin Wang; Bingyan Li; Ziye Yang; Ruo Yang; Keming Zhu; Yong Liu (Analytica Chimica Acta, 2025)

The Application of Digital Twin Technology in the Development of Intelligent Aquaculture: Status and Opportunities - Jianlei Chen; Yong Xu; Hao Li; Xinguo Zhao; Yang Su; Chunhao Qi; Keming Qu; Zhengguo Cui (Fishes, 2025)
Aquaculture is vital for global food security but faces challenges like disease, water quality control, and resource optimization. Digital twin technology, a real-time virtual replica of physical aquaculture systems, emerges as a transformative solution. By integrating sensors and data analytics, it enables monitoring and optimization of water quality, feed efficiency, fish health, and operations. This review explores the current adoption status of digital twins in aquaculture, highlighting applications in real-time monitoring and system optimization. It addresses key implementation challenges, including data integration and scalability, and identifies emerging opportunities for advancing sustainable, intelligent aquaculture practices.

Numerical and experimental study of CO2 jet impingement on curved surfaces with different phases - Qian Chen; Laibin Zhang; Jianchun Fan; Yunpeng Yang; Keming Hu; Yang Fu (Process Safety and Environmental Protection, 2025)

Predatory protist promotes disease suppression against bacterial wilt through enriching plant beneficial microbes at the early stage of plant growth - Yuqi Song; Chen Liu; Keming Yang; Shiqi Sun; Lin Wang; Cansheng Yuan; Yangchun Xu; Wu Xiong; Qirong Shen; Zhong Wei (Plant and Soil, 2025)

Network pharmacology, molecular docking, molecular dynamics simulation, and experiment verification analysis to reveal the action mechanism of RenShen Guipi Wan in the treatment of anemia - Tingli Qu; Nan Zhang; Chen Li; Xuyuan Liu; Keming Yun; Quan An (Biotechnology Letters, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Multisource remote sensing and ensemble learning for multidimensional monitoring of heavy metals on mine surfaces - Yanru Li; Keming Yang; Xinru Gu; Lishun Peng; Xinyang Chen (Environmental Geochemistry and Health, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Impacts of sedimentary characteristics and diagenesis on reservoir quality of the 4th member of the Upper Triassic Xujiahe formation in the western Sichuan basin, southwest China - Xianliang Chen; Youliang Ji; Keming Yang (Marine and Petroleum Geology, 2024)

Purification of seawater aquaculture using constructed wetlands in a recirculating aquaculture system for Pacific white shrimp (Litopenaeus vannamei) and analysis of microbial community structure - Yanyan Wang; Meimei Hu; Jianlei Chen; Hongwu Cui; Shengmin Zhu; Tongtong Jin; Keming Qu; Zhengguo Cui (Journal of Water Process Engineering, 2024)

Spatial-temporal pattern of ecosystem services and sustainable development in representative mountainous cities: A case study of Chengdu-Chongqing Urban Agglomeration - Liang Chen; Ying Yao; Keming Xiang; Xiaoai Dai; Wenyu Li; Hang Dai; Ke Lu; Weile Li; Heng Lu; Yang Zhang; Huan Huang; Meilian Wang (Journal of Environmental Management, 2024)

Meta-Analysis Study on the Role of Biochar on Soil Nitrogen Cycling - Binbin Yu; Keming Yang; Min Cui; Zilong Chen; Yuanyuan Dai; Xiaoqing Qian; Zhongzhi Chen (Journal of Soil Science and Plant Nutrition, 2024)

Extraction of vegetation disturbance range using aboveground biomass estimated from Sentinel-2 imagery in coal mining areas with high groundwater table - Kegui Jiang; Keming Yang; Xianglin Dong; Xinyang Chen; Lishun Peng; Xinru Gu (Environmental Science and Pollution Research, 2024)

Retraction Note: Renal enhanced CT images reveal the tandem mechanism between tumor cells and immunocytes based on bulk/single-cell RNA sequencing - Haote Liang; Keming Wu; Rongrong Wu; KaTe Huang; Zhexian Deng; Hongde Chen (Functional & Integrative Genomics, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Polystyrene nanoplastics affected the nutritional quality of Chlamys farreri through disturbing the function of gills and physiological metabolism: Comparison with microplastics - Yejiao Sun; Xinguo Zhao; Qi Sui; Xuemei Sun; Lin Zhu; Andy M. Booth; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

New insights into the impact of polystyrene micro/nanoplastics on the nutritional quality of marine jacopever (Sebastes schlegelii) - Xuemei Sun; Xuru Wang; Andy M. Booth; Lin Zhu; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Effect of the molecular weight of DOM on the indirect photodegradation of fluoroquinolone antibiotics - Shukai Liu; Zhengguo Cui; Dongsheng Ding; Ying Bai; Jianlei Chen; Hongwu Cui; Rongguo Su; Keming Qu (Journal of Environmental Management, 2023)

Fine mapping and candidate gene analysis of qSB12YSB, a gene conferring major quantitative resistance to rice sheath blight - Yu Wang; Quanyi Sun; Jianhua Zhao; Taixuan Liu; Haibo Du; Wenfeng Shan; Keting Wu; Xiang Xue; Chao Yang; Jun Liu; Zongxiang Chen; Keming Hu; et al. (Theoretical and Applied Genetics, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Amine-functionalized cotton for the treatment of oily wastewater - Yiling Ao; Ji'an He; Keming Chen; Mingzhao Zhu; Fan Ye; Liwei Shen; Ying Yang; Xuening Feng; Zejun Zhang; Yuqi Tang; Yuanzhu Mi (Environmental Research, 2023)

Contrasting currents drive geographic variability in the biomass of Pacific saury (Cololabis saira), zooplankton, and phytoplankton in the northwestern Pacific - Yuqiu Wei; Zhengguo Cui; Yongqiang Shi; Xiujuan Shan; Bingzhang Chen; Keming Qu; Quandong Xin; Tao Jiang; Jufa Chen (Progress in Oceanography, 2023)

Key determinants controlling the seasonal variation of coastal zooplankton communities: A case study along the Yellow Sea - Yuqiu Wei; Xueyang Chen; Ying Liu; Yingzhe Wang; Keming Qu; Jun Sun; Zhengguo Cui (Marine Pollution Bulletin, 2023)

Dietary selenium requirement for on-growing grass carp, Ctenopharyngodon idellus - Feifei Chen; Ziyi Zhang; Li Wang; Haodong Yu; Xuezhen Zhang; Keming Rong (Aquaculture, 2023)

Ocean acidification enhances the embryotoxicity of CuO nanoparticles to Oryzias melastigma - Hao Wang; Qi Sui; Jian Zhao; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2023)

RETRACTED ARTICLE: Renal enhanced CT images reveal the tandem mechanism between tumor cells and immunocytes based on bulk/single-cell RNA sequencing - Haote Liang; Keming Wu; Rongrong Wu; KaTe Huang; Zhexian Deng; Hongde Chen (Functional & Integrative Genomics, 2023)

Charge-dependent negative effects of polystyrene nanoplastics on Oryzias melastigma under ocean acidification conditions - Yufei Chen; Xia Wang; Qi Sui; Guozhu Chang; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

A reference vector based multiobjective evolutionary algorithm with Q-learning for operator adaptation - Keming Jiao; Jie Chen; Bin Xin; Li Li (Swarm and Evolutionary Computation, 2023)

Temperature-controlled microalgae biofilm adsorption/desorption in a thermo-responsive light-guided 3D porous photo-bioreactor for CO2 fixation - Yun Huang; Beiyu Zhang; Keming Chen; Ao Xia; Xianqing Zhu; Xun Zhu; Qiang Liao (Environmental Research, 2023)

Three-dimensional porous biofilm photobioreactor with light-conducting frameworks for high-efficiency microalgal growth - Weida Zeng; Keming Chen; Yun Huang; Ao Xia; Xianqing Zhu; Xun Zhu; Qiang Liao (Algal Research, 2023)

Exploring the key factors affecting the seasonal variation of phytoplankton in the coastal Yellow Sea - Yingzhe Wang; Ying Liu; Xueyang Chen; Zhengguo Cui; Keming Qu; Yuqiu Wei (Frontiers in Marine Science, 2022)
Marine phytoplankton play crucial roles in the ocean’s biological pump and have great impacts on global biogeochemical cycles, yet the knowledge of environmental variables controlling their seasonal dynamics needs to be improved further, especially in the coastal ecosystems. In order to explore the determinants affecting the seasonal variation of phytoplankton, here we conducted three surveys during spring, summer and autumn along the coastal Yellow Sea. Among the phytoplankton community, 49 species of diatoms and 9 species of dinoflagellates were observed in spring, 63 species of diatoms and 10 species of dinoflagellates in summer, and 62 species of diatoms and 11 species of dinoflagellates in autumn. These results thus suggested that there were obvious differences in the number of species across the three seasons, of which diatoms were the most diverse group, followed by dinoflagellates. Additionally, diatoms were the most dominant species of the phytoplankton community and varied largely during different seasons. According to the redundancy analysis, the abundance of phytoplankton community was mainly related to water temperature and dissolved inorganic nitrogen (DIN) during the three seasons, indicating that water temperature and DIN could be the key factors controlling the seasonal variability of phytoplankton community along the coastal Yellow Sea. Also, significant correlations were observed between phytoplankton abundance and heavy metals Zn, As, and Hg during the three seasons, suggesting that these metals also had potential influences on the seasonal dynamics of phytoplankton community in the coastal Yellow Sea.

Hydrocarbons removal and microbial community succession in petroleum-contaminated soil under hydrogen peroxide treatment - Bing Yang; Mi Zhou; Yuan Meng; Keming Chen; Jie Xu; Xiangfu Huang; Yucheng Liu; Lingli Li; Lili Ma; Mingyan Chen (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of metallic nanoparticles on the marine environments: Species sensitivity distributions analysis - Sulan Feng; Lin Zhu; Xinguo Zhao; Qi Sui; Xuemei Sun; Bijuan Chen; Keming Qu; Bin Xia (Frontiers in Marine Science, 2022)
Metallic nanoparticles (NPs) are increasingly being used and inevitably entering the marine environment. Therefore, the adverse effects of NPs on individual marine species have attracted increasing attentions. However, to date, the ecological risks of NPs on the marine ecosystem remain poorly understood. In this study, species sensitivity distributions (SSDs) were constructed for Ag, ZnO, CuO, and TiO 2 NPs to understand their ecotoxicity to the marine ecosystem and the contribution of size effect and ion effect to the nanotoxicity. Furthermore, a case study on the assessment of marine ecological risk and marine environment carrying capacity of metallic NPs was performed in Jiaozhou Bay, China. The results showed the toxicity of metallic NPs to marine species following the order of Ag > ZnO > CuO > TiO 2 . Both size effect and ion effect contributed to the toxicity of NPs. Environmental concentrations of Ag, ZnO, CuO, and TiO 2 NPs are much lower than the predicted no-effect concentrations, indicating that these metallic NPs have not yet posed risks to the marine ecosystem based on currently limited measured environmental concentrations of metallic NPs in seawater. And the marine environment carrying capacity of Ag, ZnO, CuO, and TiO 2 NPs in Jiaozhou Bay seawater were determined to be 5.03, 8.72, 93.06, and 629.79 t, respectively. The results help us understand the ecological risk of NPs in marine environments and provide a scientific basis for the sustainable development of nanotechnology.

Tsp-1 is involved in DNA stability through Tgf-β1 activation domain in cone photoreceptor 661 W cells - Pei Chen; Chang Liu; Jing Zhang; Xi Chen; Xuan Liu; Shengyu He; Anqi He; Shuilian Chen; Jin Qiu; Yan Li; Zihua Jiang; Keming Yu; et al. (Cell and Tissue Research, 2022)

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Perspective on Etiology and Treatment of Bipolar Disorders in China: Clinical Implications and Future Directions - Zuowei Wang; Chen Jun; Keming Gao; Haichen Yang; Yiru Fang (Neuroscience Bulletin, 2019)

Succession of phytoplankton functional groups from spring to early summer in the central Bohai Sea using HPLC–CHEMTAX approaches - Lin Lu; Tao Jiang; Yong Xu; Yaoyang Zheng; Bijuan Chen; Zhengguo Cui; Keming Qu (Journal of Oceanography, 2018)

Consumption of an exotic plant (Spartina alterniflora) by the macrobenthic fauna in a mangrove wetland at Zhanjiang, China - Quan Chen; Guorui Xu; Shuang Zhang; Keming Ma (Wetlands, 2018)

Intein-mediated Cre protein assembly for transgene excision in hybrid progeny of transgenic Arabidopsis - Jia Ge; Lijun Wang; Chen Yang; Lingyu Ran; Mengling Wen; Xianan Fu; Di Fan; Keming Luo (Plant Cell Reports, 2016)

A hypergraph-based context-sensitive representation technique for VHR remote-sensing image change detection - Ping Jian; Keming Chen; Chenwei Zhang (International Journal of Remote Sensing, 2016)

Important clinical features of atypical antipsychotics in acute bipolar depression that inform routine clinical care: a review of pivotal studies with number needed to treat - Keming Gao; Chengmei Yuan; Renrong Wu; Jun Chen; Zuowei Wang; Yiru Fang; Joseph R. Calabrese (Neuroscience Bulletin, 2015)

Carbon and nitrogen isotopes analysis and sources of organic matter in surface sediments from the Sanggou Bay and its adjacent areas, China - Bin Xia; Yi Cui; Bijuan Chen; Zhengguo Cui; Keming Qu; Feifei Ma (Acta Oceanologica Sinica, 2014)

Evaluation of Upper Triassic T3x5 Source Rocks (Western Sichuan Depression, Sichuan Basin) and their Hydrocarbon Generation and Expulsion Characteristics: Implication for Tight-Sand Gas and Shale Gas Accumulation Potential Assessment - Yingchun Guo; Xiongqi Pang; Dongxia Chen; Keming Yang; Zhenxue Jiang; Xiaopeng Zhang; Fujie Jiang (Natural Resources Research, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

Molecular cloning, expression and characterization of a novel vacuolar protein sorting 4 gene in silkworm, Bombyx mori - Hengchuan Xia; Chunxia Zhang; Fan Feng; Yi Yuan; Yang Zhou; Xiaoyong Liu; Keming Zhu; Qin Yao; Keping Chen (Molecular Biology Reports, 2012)

The cauliflower mosaic virus (CaMV) 35S promoter sequence alters the level and patterns of activity of adjacent tissue- and organ-specific gene promoters - Xuelian Zheng; Wei Deng; Keming Luo; Hui Duan; Yongqin Chen; Richard McAvoy; Shuiqing Song; Yan Pei; Yi Li (Plant Cell Reports, 2007)

In vitro regeneration and Agrobacterium-mediated genetic transformation of Euonymus alatus - Yongqin Chen; Litang Lu; Wei Deng; Xingyu Yang; Richard McAvoy; Degang Zhao; Yan Pei; Keming Luo; Hui Duan; William Smith; Chandra Thammina; Xuelian Zheng; et al. (Plant Cell Reports, 2006)

The maize Knotted1 gene is an effective positive selectable marker gene for Agrobacterium-mediated tobacco transformation - Keming Luo; Xuelian Zheng; Yongqin Chen; Yuehua Xiao; Degang Zhao; Richard McAvoy; Yan Pei; Yi Li (Plant Cell Reports, 2006)

Entangling the Complexity of Protected Area Management: The Case of Wolong Biosphere Reserve, Southwestern China - Bojie Fu; Kelin Wang; Yihe Lu; Shiliang Liu; Keming Ma; Liding Chen; Guohua Liu (Environmental Management, 2004)